Age specific recruitment and retention to a large multicentre observational breast cancer trial in older women: The Age Gap Trial. Issue 5 (June 2021) - Todd, Annaliza; Martin, Charlene; Morgan, Jenna; Herbert, Esther; Bradburn, Mike; Burton, Maria; Reed, Malcolm W.R.; Chater, Tim; Pemberton, Kirsty; Walters, Stephen; Cheung, Kwok Leung; Audisio, Riccardo A.; et al.
Abstract: Introduction: Recruitment and retention are two of the most important factors in successfully running clinical trials. Many trials encounter problems with both, causing delays or preventing study progress. These issues are greater in older adults and patients with cancer. Materials and methods: We assessed recruitment and retention in a large, multicentre, observational breast cancer study in older female patients (>70 years, N  = 3440). Data collected by the Age Gap study were used to assess rates of, and reasons for, patients not being recruited or retained. Statistical analysis assessed the impact of age as a predictor of recruitment and retention. Results: Between February 2013 and June 2018, 6876 patients were screened and 3456 were consented across 56 United Kingdom (UK) breast units. Reasons for non-recruitment included ineligibility, clinician issues, staffing resource issues, patients' lack of interest or time and trial burden. In comparison with the age demographics of patients with breast cancer in the UK, women aged 70–75 years were over-represented compared to older age groups. Logistic regression demonstrated that older age significantly reduced the odds of consent (OR = 0.96, CI: 0.938–0.982; p  < 0.001). Multivariate analysis showed that age (p < 0.001), markers of poor functional ability (Eastern Cooperative Oncology Group Performance Status ( p  = 0.011)) and instrumental activities of daily living ( p  = 0.026) were significant predictors of withdrawal. Discussion: This study has demonstrated that selection and attrition bias for age are apparent despite a range of 'age friendly' study design measures. Exploration of the underlying reasons for this and development of measures to address this should be the focus of further research.